Bilateral congenital cystic adenomatiod malformation of the lungs: a case report (2006)
A six weeks old infant presented with scalp ulcer and fever, and on examination was found to have resonant percussion notes bilaterally. The initial chest radiograph revealed multiple lucencies which were initially thought to be due to diaphragmatic hernia, but the dilemma was resolved by Computerized tomography which revealed the lucencies to be multiple cysts characteristics of Congenital Cystic Aaenomatiod Malformation (CCAM) type II.